The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1210/en.2012-1151
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Obesity by Repression of VEGF Gene Expression through Induction of Brown-Like Adipocyte Differentiation

Abstract: Adipose tissues are classified into white adipose tissue (WAT) and brown adipose tissue (BAT). WAT is responsible for energy storage, and malfunction is associated with obesity. BAT, on the contrary, consumes fat to generate heat through uncoupling mitochondrial respiration and is important in body weight control. Vascular endothelial growth factor (VEGF)-A is the founding member of the VEGF family and has been found highly expressed in adipose tissue. A genetic mouse model of an inducible VEGF (VEGF-A) repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 38 publications
5
59
0
Order By: Relevance
“…Notably, overexpression of Vegf in adipose tissues of mice increases BAT mass, stimulates beiging and promotes a healthy metabolic profile 93,94 . Vegf inhibition has also been shown to reduce metabolic disease in mice, although this effect was in the context of obese WAT that was already dysfunctional 94,95 . Further studies will be needed to elucidate the mechanism(s) by which VEGF manipulates the fate of adipose tissue under different metabolic states.…”
Section: Sympathetic Nerve Control Of Brown and Beige Fatmentioning
confidence: 99%
“…Notably, overexpression of Vegf in adipose tissues of mice increases BAT mass, stimulates beiging and promotes a healthy metabolic profile 93,94 . Vegf inhibition has also been shown to reduce metabolic disease in mice, although this effect was in the context of obese WAT that was already dysfunctional 94,95 . Further studies will be needed to elucidate the mechanism(s) by which VEGF manipulates the fate of adipose tissue under different metabolic states.…”
Section: Sympathetic Nerve Control Of Brown and Beige Fatmentioning
confidence: 99%
“…Serum levels of VEGF-A are raised during obesity (9)(10)(11) and rapidly decrease following bariatric surgery (10), suggesting that elevated VEGF is deleterious. In support of this Lu et al (12) showed that VEGF knockdown suppressed obesity and promoted "browning" of white adipose tissue (WAT). In contrast, reports using adipose-specific VEGF transgenic or knockout mice suggest that increased expression of VEGF is beneficial during obesity (12)(13)(14)(15).…”
mentioning
confidence: 82%
“…In support of this Lu et al (12) showed that VEGF knockdown suppressed obesity and promoted "browning" of white adipose tissue (WAT). In contrast, reports using adipose-specific VEGF transgenic or knockout mice suggest that increased expression of VEGF is beneficial during obesity (12)(13)(14)(15). This is further complicated by contradictory reports depending on the model system; Sun et al (13) found that antibody neutralization of VEGF impaired metabolic homeostasis in a dietary model of obesity but improved glucose tolerance in a genetic (ob/ob) model.…”
mentioning
confidence: 82%
“…The specificity of amplification was confirmed by melting curve analysis and gel electrophoresis. All results were normalized to the levels of 18S ribosomal (r)RNA, and relative quantification was calculated using relative quantification (ΔΔCq) values for each biological replicate (16,17). Values are expressed as the mean ± standard error of the mean (SEM; triplicate samples and three repeats).…”
Section: Methodsmentioning
confidence: 99%